Strategi Pendidikan Islam Menghadapi Kemajuan Iptek - M Slamet Yahya (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Nowadays, Islamic education experience functional degradation because unable to show itsreal spirit. Islamic education just only can adapt to the education orienting at materialistic (pragmatic and practical) aspect, so that unable to determine its step independently. In order to follow science and technology development, there’s three aspects, namely knowledge oriented, skill oriented, and values oriented. Thereby the target of short-range (world bliss) and long-range target (akherat bliss) of Islamic education can be reached. Here also conducted comparative analysis to thought of education figures (especially Islamic education) so that we can found concept or theory of Islamic education which not only orienting at cognitive aspect, but also orienting at student moral aspect, and also can keep abreast of the science and technology, and keep stand on Islamic values.